Football Hero - Green, Tim 1963- (New York : HarperCollinsPublishers, 2008)
When twelve-year-old Ty's brother Thane is recruited out of college to play for the New York Jets, their Uncle Gus uses Ty to get insider information for his gambling ring, landing Ty and Thane in trouble with the Mafia.
Keywords: Football -- Fiction; Brothers -- Fiction; Conduct of life -- Fiction; Family life -- Fiction -- New Jersey; Organized crime -- Fiction; New Jersey -- Fiction; New York (N.Y.) -- Fiction